Analisis Kesalahan Mahasiswa dalam Menentukan Besar Sudut pada Bangun Datar - Brilyant Alvindo Sihombing; Fithrah Amalia Sirait; Devita Syahputri; Dinda Rizky; Siti Aisyah Lubis; Novitasari Br Hutauruk; Muhammad Amin Fauzi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the types of student errors in solving problems on determining the size of angles in flat shapes. The subjects of the study were students of the Mathematics Education Study Program, State University of Medan, academic year 2024/2025. Data were obtained through written tests and interviews with 10 students. The results of the study showed that the errors often made by students included conceptual errors (42%), procedural errors (38%), and computational errors (20%). Conceptual errors are mainly related to understanding the relationship between angles in triangles and supplementary angles, procedural errors are related to unsystematic solution steps, while computational errors are errors in making calculations. This study provides recommendations to improve students' conceptual understanding of angles and their relationships in flat shapes.